Serum Metrnl levels are decreased in subjects with overweight or obesity and are independently associated with adverse lipid profile - Ding, Xiaoyu; Chang, Xiaona; Wang, Jiaxuan; Bian, Nannan; An, Yu; Wang, Guang; Liu, Jia (Frontiers in Endocrinology, 2022)
Background: Meteorin-like (Metrnl), a novel adipokine, is highly expressed in adipose tissue and has a beneficial effect on energy metabolism. However, data on circulating Metrnl levels in obesity are scarce and inconsistent. This study aimed to evaluate the serum levels of Metrnl in adults with obesity and its association with glucose and lipid metabolism. Methods: 182 subjects were included in the cross-sectional study. The participants were divided into three groups according to BMI: normal (n = 95), overweight (n = 46), and obesity (n = 41). Serum Metrnl concentrations were measured by enzyme-linked immunosorbent assay. Results: Serum Metrnl levels in overweight or obese subjects were significantly lower than in the normal group. Circulating Metrnl levels were negatively correlated with TG, TC, LDL-C, and sdLDL and positively correlated with HDL-C before and after adjusting for age, sex, BMI, diabetes, HOMA-IR, and eGFR (all P < 0.05). Furthermore, logistic regression analysis indicated that compared with the highest tertile, the lowest tertile of Metrnl levels were significantly associated with the presence of hyper-TG, hyper-TC, and Hyper-LDL after full adjustment (all P for trend < 0.05). Conclusions: Serum Metrnl levels were reduced in individuals with overweight or obesity and were independently associated with adverse lipid profile, suggesting that modifying circulating Metrnl levels may serve as a potential therapeutic target for atherogenic dyslipidemia.